(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Cervical cancer and tuberculosis remain significant health concerns, the former is associated with high levels of morbidity and mortality. Case presentation: A 37-year-old nulliparous woman presented to the gynecological ward with a five-year history of intermittent per vaginal bleeding, post- coital bleeding, and intermenstrual bleeding associated with per vaginal discharge and dyspareunia. She had a friable cervical mass on speculum examination, and cervical cancer was suspected. The patient was examined under anesthesia, and a biopsy of the mass was performed. Histological examination revealed cervical tuberculosis. The patient was started anti- tuberculosis therapy for six months and responded well. Conclusion: Cervical tuberculosis should be considered as a differential diagnosis for cervical masses, as seen in this rare case of cervical tuberculosis that mimicked cervical cancer. A high index of suspicion is required for timely diagnosis and treatment.